Collapse and Revival of an Artificial Atom Coupled to a Structured Photonic Reservoir - Vinicius S. Ferreira; Jash Banker; Alp Sipahigil; Matthew H. Matheny; Andrew J. Keller; Eunjong Kim; Mohammad Mirhosseini; Oskar Painter (Physical Review X, 2021)
Quantum emitters in the presence of an electromagnetic reservoir with varying density of states, or structure, can undergo a rich set of dynamical behavior. In particular, the reservoir can be tailored to have a memory of past interactions with emitters, in contrast to memoryless Markovian dynamics of typical open systems. In this article, we investigate the non-Markovian dynamics of a superconducting qubit strongly coupled to a superconducting waveguide engineered to have both a sharp spectral variation in its transmission properties and a slowing of light by a factor of 650. Tuning the qubit into the spectral vicinity of the passband of this slow-light waveguide reservoir, we observe a 400-fold change in the emission rate of the qubit, along with oscillatory energy relaxation of the qubit resulting from the beating of bound and radiative dressed qubit-photon states. Furthermore, upon addition of a reflective boundary to one end of the waveguide, we observe revivals in the qubit population on a timescale 30 times longer than the inverse of the qubit’s emission rate, corresponding to the round-trip travel time of an emitted photon. By in situ tuning of the qubit-waveguide interaction strength, we also probe a crossover between Markovian and non-Markovian qubit emission dynamics in the presence of feedback from waveguide reflections. With this superconducting circuit platform, future studies of multiqubit interactions via highly structured reservoirs and the generation of multiphoton highly entangled states are possible.